Jellyfish-human interactions in North Carolina - Kaneshiro-Pineiro, Mahealani Y. (East Carolina University, 2013)
This dissertation investigated potential drivers of jellyfish-human interactions in North Carolina. Jellyfish populations and human use of coasts are increasing; therefore, jellyfish-human interactions are poised to become more frequent. This research investigated how abiotic variables (i.e. temperature and salinity) and wind-driven circulation in the Neuse River Estuary influenced the distribution and abundance of the sea nettle, Chrysaora quinquecirrha, at six recreational sites. Life history traits were also investigated to determine if jellyfish aggregations at the recreation sites could be linked to sexual reproduction. Finally, the human perspective on jellyfish was investigated. One hundred eighteen people were surveyed at 25 coastal locations prone to jellyfish occurrences. This survey used cultural consensus theory to gather perspectives of jellyfish ecology and how jellyfish influence society from four cultural groups: fishers (commercial and recreational), recreationists (surfers, swimmers, etc.), North Carolina coastal researchers, and jellyfish researchers in the United States. Results show: 1) southwest winds 3 to 8 meters per second that occurred 1 and 5 days prior to observations resulted in more sea nettles observed at the Neuse River Estuary recreation sites; 2) aggregations of sea nettles resulting from wind events could not be definitively linked to sexual reproduction based on jellyfish gonad analysis; 3) cultural perspectives of jellyfish ecology were different among groups; this was most obvious when the role of jellyfish in food webs was evaluated. All groups shared similar societal perspectives, including tolerance to specific numbers of jellyfish. Overall, this research has identified physical, ecological and societal factors that influence jellyfish-human interactions in North Carolina and these interactions appear to be mediated by several different factors. Understanding these factors will allow for management of jellyfish-human interactions. Recreational areas subjected to high sea nettle occurrences based on local oceanographic conditions may employ barrier nets to decrease the frequency of encounters. Further studies into the dominant mode of reproduction for sea nettles may indicate which life history stage, polyp or medusa, might be the best target for management to reduce jellyfish-human interactions. Finally, outreach education about common misconceptions concerning jellyfish may remove some confusion surrounding the role of these organisms in the environment.
Keywords: Ecology; Cultural anthropology; Environmental management; Chrysaora quinquecirrha; Cultural consensus theory; Gonad maturity; Jellyfishes; Sea nettles; Wind; Biology, Ecology; Sea nettle--North Carolina--Neuse River Estuary; Environmental management--North Carolina--Neuse River Estuary